P75 Exploring public awareness and understandings of cancer through qualitative Methods. (13th September 2016) - Green, T; Bailey, L; Sinclair, H; Macdonald, S; Macleod, U
Abstract : Background: In terms of morbidity and mortality, cancer remains one of the UK's biggest health problems. Because of this, there has been considerable focus from policymakers and charitable bodies alike on raising awareness of cancer symptoms among the lay-public. Whilst awareness of symptoms for different cancers does seem to have filtered through to some areas of the public domain, the perception of cancer as a 'death sentence' has not been fully dispelled. The problem is to understand why, despite the continued efforts of campaign organisers to promote the advantages of early symptom detection on survival rates for some cancers, the term 'cancer' itself retains a powerfully negative status within the public consciousness. Methods: We are conducting a series of focus groups and semi-structured interviews in a northern city of the UK with higher than average cancer mortality rates. Participants are members of the public who have not been diagnosed with cancer. The study sample is a mixed cohort with regard to gender, age and socio-economic status. Our inquiry focuses on participants' awareness of cancer symptoms, their understandings of cancer risk and cause, their perceptions of awareness campaigns, and their experiences of help-seeking and consequent behaviour. Results: Although data collection and analysis are ongoing, early findings from five focus groups and 12 interviews conducted so far demonstrate a distinction with regard to cancer and mortality between participants who perceive cancer as an 'umbrella-term' for a multiplicity of cancers with a range of symptoms and outcomes, and participants who perceive cancer as a singular, random disease that can strike anyone at any time, with death the inevitable outcome. These latter perceptions have emerged across the study sample, despite participants' experiences of family members/friends who have survived different cancers. Conclusion: Campaigns to raise awareness of different cancers among the general public that continue to emphasise the positive impact earlier detection can have on treatment and survival should continue. However, there is also a need to employ strategies that might dispel notions of cancer as an inevitable 'death sentence'. As GPs are promoted through campaigns as the first port of call for people with worrying symptoms, it would seem sensible to explore how practitioners within primary care could foster more nuanced understandings of different cancers.